Cases of RhD variants RhD*DAU2/DAU6 and RhD*weak D type 4.1 in pregnant women in Saudi Arabia - Owaidah, Amani; Aljuhani, Khadijah; Albasri, Jasem; Alsulmi, Eman; Alsaihati, Taibah; Alzahrani, Faisal (Acta Biomedica Atenei Parmensis, 2023)
The D antigen is one of the most immunogenic and clinically significant antigens of the Rh blood group system due to its various genotypes that encode for more than 450 different variants. Accurate RhD typing and D variant identification is crucial specially in prenatal screening during pregnancy. Women with RhD -ve phenotype are eligible to Rh immune globulin (RhIG) prophylaxis for the prevention of anti-D alloimmunization and hemolytic disease of the fetus and newborn (HDFN). However, there are some women who possess RhD variant alleles, who are mistakenly grouped as RhD positive and considered not eligible for RhIG prophylaxis, putting them at risk of anti-D alloimmunization and consequently leading to HDFN during subsequent pregnancies. Here, we describe  two cases of RhD variants DAU2/DAU6 and Weak D type 4.1 in obstetric patients who were grouped as RhD +ve with negative antibody screening during routine serologic  testing. Weak/Partial D molecular analysis using genomic DNA Red Cell Genotyping (RCG) revealed that both patients had RhD variants, one of which DAU2/DAU6 allele associated with anti-D alloimmunization. According to routine testing neither patients received RhIG or transfusion. In this case report we document to our knowledge the first reported cases of RhD variants among pregnant women in Saudi Arabia.